Manejo de residuos sólidos municipales en la localidad de Roque - Fernández Requejo, Elvis Luis (2011)
The present fact~finding project tries to improve the handling system of Residuos Sólidos in those cities and localities with rural qualifications, and those that he finds under urban consolidation as present case comes from the locality of Roque, the same one that belongs to province of Lamas, department San Martin -Perú, in such sense 1 put in Alonso de Alvarado power of the municipality of Alonso de Alvarado district with his capital Roque a modest study on the steps of the municipal Residuos Sólidos, the same ones than music generados so in The urban part and said- locality Periurbana, in her asit happens to me that the solid leavings's study of true basic parameters in the operating handling and technician is emphasized, for everything itas, show it(subj) investigation tries to generate valuable information that he allow him to(subj) an authorities on duty to take the more coherent decisions in regards to the environmental and sanitary policy of Roque locality, the same one that he permit (subj) constituting in the Environmental steps's preventive and control's instrument. 1 am pleased to finalize in this first context in to have culminated to intend to get better pioneer and contributing in this little localized ecosystem's harmonious and healthy Desarrollo herein splits of her with the objective Región San Martin, 2010.